Kontekstualisme Awal: Tafsir Khalīfah ‘Umar Bin Al-Khaṭṭāb dari Studi Historis Sampai Langkah Metodologis - Althaf Husein Muzakky (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
The study of Umar Bin al-Khaṭṭāb is often studied as the second caliph of Islam, but the role of Umar Bin al-Khaṭṭāb in contextual interpretation is enormous. This paper aims to examine the historical and methodological understanding of early contextualism in the world of al-Qur'an interpretation. through the study of the epistemology of Abid al-Jabiri approach, this research resulted in two conclusions. first, history, the contextual interpretation of the Koran has developed even since the time of the caliph 'Umar Bin al-Khaṭṭāb. Second, the method of contextual interpretation of the friend 'Umar Bin al-Khaṭṭāb is to dialogue between text and context, prioritizing benefit and being objective.